Translanguaging Practices in Indonesian Pop Songs - Purnama Nancy Lumban Batu; Katharina Sukamto (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This paper focuses on the practice of translanguaging in Indonesian pop songs and highlights the possible reasons behind the practice. In this study, translanguaging is viewed from the context of the Indonesian singers’ linguistic repertoire, which allows varieties in the production (Canagarajah, 2013) of the songs. Three pop songs, composed by the singers themselves, are used for samples. The result indicates that translanguaging, performed using Indonesian and English, is utilized by the artists as a strategy to exercise their agency, either as Indonesian artists or as members of the global society. Translanguaging in the pop songs is not merely seen as a commercial activity, but it is also a deliberate practice which will attract the attention of the audience. The reasons behind the translanguaging practice indicate three things, namely (1) as a means to convey a cultural message, (2) as a means for meaning-making, and (3) as a means of gaining fame.